Evolution of the porous structure of cocoa beans during microwave drying. Issue 10 (1st July 2020) - Alean, Jader; Chejne, Farid; Maya, Juan C.; Camargo-Trillos, Diego; Ramírez, Say; Rincón, Edgar; Rojano, Benjamin
Abstract: In this work, it was evaluated the morphological changes of the porous structure of the cocoa bean samples subjected to microwave drying. The use of microwaves (MWs) applied by ON-OFF on cocoa bean samples allowed to avoid both the burning and the roasting of the beans. During the MWs drying process, phenomena of breakage of cellular structure, coalescence and, pore plugging altered the average pore diameter, the pore volume, surface area, and Pore Size Distribution (PSD). When the results of sun-dried beans were compared with those of beans dried by MWs, it was concluded that the average pore diameter, the pore volume, the surface area and, PSD were also affected by the solar drying; however, the breakage of cellular structure did not occur.